Telomeres and telomerase in hematopoietic dysfunction: Prognostic implications and pharmacological interventions - Vasko, Theresa; Kaifie, Andrea; Stope, Matthias B.; Kraus, Thomas; Ziegler, Patrick (International Journal of Molecular Sciences, 2017)
Leukocyte telomere length (TL) has been suggested as a marker of biological age in healthy individuals, but can also reflect inherited and acquired hematopoietic dysfunctions or indicate an increased turnover of the hematopoietic stem and progenitor cell compartment. In addition, TL is able to predict the response rate of tyrosine kinase inhibitor therapy in chronic myeloid leukemia (CML), indicates clinical outcomes in chronic lymphocytic leukemia (CLL), and can be used as screening tool for genetic sequencing of selected genes in patients with inherited bone marrow failure syndromes (BMFS). In tumor cells and clonal hematopoietic disorders, telomeres are continuously stabilized by reactivation of telomerase, which can selectively be targeted by telomerase-specific therapy. The use of the telomerase inhibitor Imetelstat in patients with essential thrombocythmia or myelofibrosis as well as the use of dendritic cell-based telomerase vaccination in AML patients with complete remissions are promising examples for anti-telomerase targeted strategies in hematologic malignancies. In contrast, the elevation in telomerase levels through treatment with androgens has become an exciting clinical intervention for patients with BMFS. Here, we review recent developments, which highlight the impact of telomeres and telomerase targeted therapies in hematologic dysfunctions.
CRIS-Team Scopus Importer:2023-09-25
Keywords: Hematologic dysfunction; Telomerase; Telomere